Peningkatan Perkembangan Seni Melalui Media Kertas Kokoru Pada Anak Usia 5-6 Tahun - Nurul Mawaddah; Syarifah Halifah; Fidrayani; Andi Tien Asmara Palintan (Universitas Muhammadiyah Metro, 2026)
This research aims to evaluate the effectiveness of Kokoru paper media in developing the artistic abilities of children aged 5-6 years at PGRI Soreang Kindergarten, Parepare City. The method applied is Classroom Action Research (PTK) using Kemmis and McTaggart techniques, which is carried out in two cycles. Each cycle includes four stages, namely planning, implementation, observation and reflection. This research consisted of 18 children from group B. Data accumulation was applied through observation, interviews and documentation techniques. The findings of this research indicate a significant increase in children's artistic abilities after the application of Kokoru paper media. In Cycle I, the activity of making pencil decorations allows children to explore the color and texture of paper. However, the majority of children are still in the Not Yet Developing (39%) and Starting to Develop (33%) categories. In Cycle II with the theme animal faces, children showed an increase in activity, imagination and confidence in expressing ideas independently. This is indicated by an increase in the proportion of children in the categories Developing Very Well (44%) and Developing According to Expectations (39%). Based on the results of the Paired Sample T-Test, a significance value of 0.000 < 0.05 was obtained, which can prove that Kokoru paper media has proven to be effective in developing creativity, fine motor skills and artistic expression in early childhood